STRES DAN KOPING ORANGTUA DENGAN ANAK RETARDASI MENTAL - Prasa, Bima Adi (EMPATHY Jurnal Fakultas Psikologi, 2012)
ABSTRACTParents who have children with mental retardation will definitely experience a variety of different challenges compared with parents who have normal children. Various sources of their stress is different with parents in general. This study aims is to find out what the source of stress and coping resources of parents. How can parents deal with coping existing sources of stress. The research method that was used is a qualitative research approach case study. Subjects were two parents of different character and backgrounds, but both have a mentally retarded child. The first subject is A who have several children. The second subject is B a single parent mother who lives alone with the only her child mental retardation. Data was collected by semi-structured interviews and nonparticipant observation. Results showed that the sources of stress of parent comes from the internal factors and external factors. The sources of coping that was used by parent can be broken down into five aspects such as social support, values and beliefs, control self-confidence, and self esteem. Effort coping strategies used include planning problem solving, positive assessment, distancing, self-control, seeking social support, and accept responsibility.Keywords: Stress, coping, parents with mentally retarded children.